Os efeitos iniciais da implantação do PROEJA no IFPB Campus Cajazeiras: o que revelam as percepções discentes? - Mendes, Claudenice Alves (2010)
This paper presents an analysis of the initial effects of the implantation of the Integration Program of Professional Education with the Basic Education in the Modality Young and Adult Education (PROEJA), in the Federal Institute of Education, Science and Technology of Paraiba Campus Cajazeiras, from the perception of the teachers involved in the Program. The students who participated of the first class of the Integrated Course of Qualification in Microcomputers Operation, implanted in the referred institution in 2007 were privileged. The inventoried themes along the research were discussed from the official documents about Young and Adult Education, as the Law CNE/CEB nº 11/2000 (BRAZIL, 2000), from the Base Document of PROEJA (BRAZIL, 2007) and from other authors who discuss PROEJA, such as: Moura (2006), Santos (2006), Machado (2006) and authors who treat EJA, such as: Freire (2000), Gadotti (2007), Arroyo (2007), Paiva (2009) among others. The goals pursued, during the research, consisted of: describing the process of implantation of PROEJA in the referred Institution, emphasizing its main challenges; highlighting traces which characterize the students of the pioneer class of PROEJA in IFPB Campus Cajazeiras, identifying its initial expectances regarding the Program, to confront them with the expectances lived in the classroom and analyzing the school results referent to the referred class, highlighting the difficulties faced by the students who have remained in the program. Based, mainly, in a qualitative approach, this investigation had its data collected through a semistructured interview, complemented with information extracted from an individual file and a diagnostic evaluation, both applied to the students during the course. The analyzed data reveal that the implementation of PROEJA in the locus of the research has happened in the middle of a series of difficulties, both related to the school context and the life and work context of the students which, summed up, make it difficult for the individuals of EJA to be included in the school space and to be able to complete successfully high school integrated to a quality professional formation.